Unilateral versus bilateral nodal irradiation: Current evidence in the treatment of squamous cell carcinoma of the head and neck. Issue 9 (19th April 2021) - Nuyts, Sandra; Bollen, Heleen; Eisbruch, Avrahram; Corry, June; Strojan, Primoz; Mäkitie, Antti A.; Langendijk, Johannes A.; Mendenhall, William M.; Smee, Robert; DeBree, Remco; Lee, Anne W. M.; Rinaldo, Alessandra; et al.
Abstract: Cancers of the head and neck region often present with nodal involvement. There is a long‐standing convention within the community of head and neck radiation oncology to irradiate both sides of the neck electively in almost all cases to include both macroscopic and microscopic disease extension (so called elective nodal volume). International guidelines for the selection and delineation of the elective lymph nodes were published in the early 2000s and were updated recently. However, diagnostic imaging techniques have improved the accuracy and reliability of nodal staging and as a result, small metastases that used to remain undetected and were thus in the past included in the elective nodal volume, will now be included in high‐dose volumes. Furthermore, the elective nodal areas are situated close to the parotid glands, the submandibular glands and the swallowing muscles. Therefore, irradiation of a smaller, more selected volume of the elective nodes could reduce treatment‐related toxicity. Several researchers consider the current bilateral elective neck irradiation strategies an overtreatment and show growing interest in a unilateral nodal irradiation in selected patients. The aim of this article is to give an overview of the current evidence about the indications and benefits of unilateral nodal irradiation and the use of SPECT/CT‐guided nodal irradiation in squamous cell carcinomas of the head and neck.